2016
DOI: 10.1186/s12875-016-0555-3
|View full text |Cite
|
Sign up to set email alerts
|

Having a usual source of care and its associated factors in Korean adults: a cross-sectional study of the 2012 Korea Health Panel Survey

Abstract: BackgroundUsual source of care (USC) is one of the hallmarks of primary care. We aimed to examine the status of having a USC and its patient-related sociodemographic factors among Korean adults.MethodsData were obtained from the 2012 Korea Health Panel survey. Panel participants were selected for the study who were aged 18 years or older and who replied to questionnaire items on having a USC (n = 11,935).ResultsOf the participants, 21.5% had a usual place and 13.9% had a usual physician. Reasons for not having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 20 publications
2
20
1
Order By: Relevance
“…Furthermore, since all studied participants have been covered by the New Rural Cooperative Medical Scheme, we did not include insurance coverage as a necessary enabling factor. Finally, although not shown in this figure, factors that would influence whether patients have a usual primary care provider include age, gender, education, culture, family economic status, health status, perceived quality of health care and patients’ attitudes toward primary care providers [ 30 , 31 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, since all studied participants have been covered by the New Rural Cooperative Medical Scheme, we did not include insurance coverage as a necessary enabling factor. Finally, although not shown in this figure, factors that would influence whether patients have a usual primary care provider include age, gender, education, culture, family economic status, health status, perceived quality of health care and patients’ attitudes toward primary care providers [ 30 , 31 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…The method of remuneration is mainly based on fee-for-service so that physicians lack an incentive to focus on reducing unnecessary services and focusing more on disease prevention and health promotion [ 16 , 17 ]. A national representative survey in 2012 reported that only 13.9% of Korean adults aged 18 years and older had a physician as a USC [ 18 ], in contrast with the proportions of other countries: the USA 80%, Canada 84%, Australia 88%, the United Kingdom and New Zealand 89% each, Germany 92%, and the Netherlands 100% [ 19 ]. It seems natural that Korea had the highest frequency (16.0) of doctor consultations per person among the OECD countries compared with the OECD average of 6.9 per person per year in 2015 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Korean patients experience much poorer health care coordination than those in other industrialized countries ( 31 ). Regarding the coordination of care that patients experience from their RDs, the percent of those who answered positively is only 34.5% in Korean adults in a previous study ( 23 ). In our study, it was only 27.1% in Korean diabetic adults.…”
Section: Discussionmentioning
confidence: 79%
“…The 2007 international survey by the Commonwealth Fund has reported that the proportion of adults who have a RD is 100% in the Netherlands, 89% in the United Kingdom, 88% in Australia, 92% in Germany, 89% in New Zealand, 84% in Canada, and 80% in the United States ( 30 ). Compared to these countries, the proportion of adults who have a RD is extremely low (13.9%) in Korea ( 23 ). This study showed that, even in adults having diabetes as a chronic disease, the percentage of those having a RD was very low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation